Evaluation of Metro Kapsul Performance in Steady State Curving, Traction, and Braking - Budiwantoro, Bagus; Herman, Indria; Halim, Fernando Sanjaya Sulaiman (ITB Journal Publisher, LPPM ITB, 2018)
Transportation is an important life aspect to save travel time from one place to another. However, traffic congestion is a major problem. Therefore, PT TReKKa intends to develop Metro Kapsul, a mass public transportation system that is suitable for densely populated developed cities. A series of technical analyses and evaluations is necessary to ensure vehicle safety in steady-state curving, traction, and braking. The maximum velocity and acceleration/deceleration in these conditions can be used to decide the development and manufacturing process of Metro Kapsul. The analyses consisted of theoretical and numerical simulations. The theoretical analysis involved applying force equilibrium condition of a rigid body. The simulation was modeled according to a real model of Metro Kapsul. The results showed that both values could be categorized as comfortable based on ASCE 21.2-2008. From this study, the safe longitudinal acceleration and deceleration of Metro Kapsul were obtained, i.e. 0.90 m/s2 and 0.97 m/s2, respectively, while the emergency longitudinal deceleration is 1.25 m/s2. When cornering, the maximum velocity is limited by the centrifugal acceleration, which is 0.6 m/s2. To conclude, the current design of Metro Kapsul is already good in steady-state performance. Further research is required for full dynamic and transient conditions with track irregularities.